Question #e4173

1 Answer
Apr 30, 2017

The current gain is beta = 49

Explanation:

Given: I_0/I_E =0.98" [1]"

We know that the output current is the current gain beta multiplied by the base current:

I_0 = betaI_b" [2]"

We know that the emitter current is the output current plus the base current:

I_E = I_0+ I_b

I_E = betaI_b+ I_b" [3]"

Substitute equations [2] and [3] into equation [1]:

(betaI_b)/(betaI_b+I_b) = 0.98

beta/(beta+1) = 0.98

1 -1/(beta+1) = 0.98

beta+1 = -1/(0.98-1)

beta+1 = 50

beta = 49